2018
DOI: 10.2106/jbjs.17.01163
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Postoperative Opioid-Prescribing Practices Following Commonly Performed Orthopaedic Hand and Wrist Surgical Procedures

Abstract: Background: Although orthopaedic surgeons have been shown to prescribe excessive amounts of opioid analgesics postoperatively, the degree in which surgical trainees contribute to this trend is unknown. The purpose of this study was to compare self-reported opioid-prescribing behavior, factors influencing this behavior, and perceptions of patient opioid utilization and disposal between hand surgeons and trainees. Methods: Attending hand surgeons and trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…Within academic medical centers, surgical residents and interns are frequently responsible for managing postoperative analgesia 3 . However, trainees tend to have the largest variability in prescribing practices among all members of the surgical team 3,25 . In a survey of 1,300 orthopedic and plastic surgeons performing four common hand surgeries, residents reported a greater tendency to prescribe higher‐potency opioids and in higher doses than attending surgeons and fellows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within academic medical centers, surgical residents and interns are frequently responsible for managing postoperative analgesia 3 . However, trainees tend to have the largest variability in prescribing practices among all members of the surgical team 3,25 . In a survey of 1,300 orthopedic and plastic surgeons performing four common hand surgeries, residents reported a greater tendency to prescribe higher‐potency opioids and in higher doses than attending surgeons and fellows.…”
Section: Discussionmentioning
confidence: 99%
“…A rapidly growing body of research has demonstrated multiple strategies for reducing postoperative opioid prescriptions, including reducing pill counts, inclusion of nonopioid alternatives, focused patient and provider education as well as preoperative medication regimes. 17‐24 However, within academic medical centers, the nearly 135,000 residents training across all specialties frequently serve as the primary prescribers of postoperative pain control regimens 3,15,25,26 . Resident physicians rarely receive formal training in opioid prescription management and most report low levels of comfort with prescribing these medications 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most opioid medications prescribed by surgeons are prescribed by trainees, 41 and although we recognize that residents are not permitted to prescribe opioids without direct attending oversight, previous studies have indicated that, in practice, resident prescribing occurs most commonly without direct communication with the attending. 42 Third, the lack of resources in Haiti poses challenges for the interpretation of our comparative study. 43 However, most responding Haitian residents (73%) believed that their indicated prescriptions were sufficient to manage postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis relates to differences in advertising, as opioid advertising is heavily curtailed in the Netherlands 24 , whereas aggressive pharmaceutical advertising in the U.S. has been posited as a potential contributor to the opioid epidemic 25 . Differences in analgesia training for residents may also contribute, although prior work indicates little training is provided to residents in either country [26][27][28] . Another potential contributing factor may be differences between Dutch and U.S. pain protocols, although this hypothesis remains subject to debate as no prior systematic comparison has been identified in the literature and Dutch protocols have been found to vary widely 29 .…”
Section: Discussionmentioning
confidence: 99%